2013
DOI: 10.1007/s11010-013-1891-4
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 2 is upregulated in colorectal cancer and contributes to colorectal cancer cells’ survival by protecting cells from oxidative stress

Abstract: Peroxiredoxin 2 (Prdx2) is a member of the peroxiredoxin family, which is responsible for neutralizing reactive oxygen species. Prdx2 has been found to be elevated in several human cancer cells and tissues, including colorectal cancer (CRC), and it influences diverse cellular processes involving cells' survival, proliferation, and apoptosis, which suggests a possible role for Prdx2 in the maintenance of cancer cell. However, the mechanism by which Prdx2 modulates CRC cells' survival is unknown. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…The dual action of PRDX2 in tumorigenesis has been demonstrated in a CRC model. Lu et al (94), in contrast with what was reported by Feng et al (86), demonstrated that PRDX2 overexpression in CRC tissues was strongly correlated with a more aggressive cancer behavior, tumor metastasis and the tumor-node-metastasis (TNM) stage, indicating a possible role for PRDX2 in CRC progression. Taken together, these data suggest that the mechanism by which PRDX2 exerts its oncogenic action is still poorly understood, and further studies are required.…”
Section: Prdxs In Tumorigenesismentioning
confidence: 92%
“…The dual action of PRDX2 in tumorigenesis has been demonstrated in a CRC model. Lu et al (94), in contrast with what was reported by Feng et al (86), demonstrated that PRDX2 overexpression in CRC tissues was strongly correlated with a more aggressive cancer behavior, tumor metastasis and the tumor-node-metastasis (TNM) stage, indicating a possible role for PRDX2 in CRC progression. Taken together, these data suggest that the mechanism by which PRDX2 exerts its oncogenic action is still poorly understood, and further studies are required.…”
Section: Prdxs In Tumorigenesismentioning
confidence: 92%
“…Several studies have indicated that PRDXs overexpression in cancer tissues strongly correlates with a more aggressive cancer behavior, tumor metastasis and the tumor-node-metastasis (TNM) stage, indicating a possible role in tumorigenesis progression [10]. PRDXs contain protein composed of 6 mammalian PRDXs, namely PRDX I to VI [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PRDXs, PRDX2 has been demonstrated to form disulfide-linked homodimers during its catalytic cycle (2). The expression of PRDX2 is unregulated in breast cancer, cervical cancer and colorectal cancer (3)(4)(5)(6). By contrast, silencing of PRDX2 occurs in acute myeloid leukemia and malignant melanomas (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The pro-tumorigenic role of PRDX2 may be attributed to, at least partially, protecting cells from oxidative stress (3)(4)(5)(6). Under oxidative stress, reactive oxygen species (ROS) also contribute to tumor necrosis factor-α (TNF-α)-induced cell death (9).…”
Section: Introductionmentioning
confidence: 99%